PENGARUH INSTITUTIONAL IMAGE TERHADAP STUDENTS LOYALTY MELALUI WORD OF MOUTH DI UNISSULA SEMARANG - La Ode Sugianto; Umi Farida (Jurnal Manajemen dan Pemasaran Jasa, 2016)
The purpose of this paper is to investigate the impact of institutional image on students loyalty trough word of mouth at Sultan Agung Islamic University. The type of research used in this study is hypothesis testing. The instrument used in this study was a questionnaire. After distributing the relevant questionnaires among 99 students, all usable questionnaires are returned. Then the data collections are analyzed by using Structural Equation Modeling (SEM). Research findings show that institutional image has a positive significant effect on word of mouth and students loyalty. Then, word of mouth has a positive significant effect on loyalty. The research has given description well that Institutional Image and word of mouth variables still give positive contribution toward students loyalty in Sultan Agung Islamic University.